(untitled) (British Journal of Global Ecology and Sustainable Development, 2025)
This article analyzes the clinical features of pregnancies complicated by eclampsia and its impact on maternal and fetal health. Based on clinical observations, laboratory data, and international literature, the risks of eclampsia for both mother and child are highlighted. The importance of early diagnosis, modern treatment approaches, and preventive measures is emphasized.